CRITIQUE OF COSTA RICAN LITERARY CRITICISM - Alfaro Vargas, Roy (2013)
This article analyses the role of Costa Rican literary criticism in relation to the Costa Rican socio-economic context. For that, besides, it is studied the academic production of several researches belonging to the Universidad de Costa Rica and the Instituto Tecnológico de Costa Rica. I propose, through the notion of positive reading, there is a disconnection between the Costa Rican context and the labour realized by the Costa Rican literary criticism.